Performance and scalability of mobile wireless base-station-oriented networks. - Milner, Stuart D.
This paper focuses on the performance and scalability of mobile, base-station-oriented wireless networks, which have been the subject of research and development projects sponsored by the Defense Advanced Research Projects Agency. The background and rationale for such networks is presented as well as performance and scalability analyses of their routing, mobility, and quality of service models. Using systems-oriented, large-scale discrete event simulation, both performance scalability and complexity scalability are analyzed. Performance scalability addresses the effect of network size on system performance. Complexity scalability, in this case, consists of communication complexity (i.e., amount of control information exchanged to create and maintain network connectivity). Results confirmed that the scalability of base station oriented networks using the routing, and mobility model, and the quality of service models enhanced performance, using over 2,000 fully dynamic hosts and routers.